Deconstructing the Power Dynamics of Prison Research - Barragan, Melissa (The prison journal, 2023)
This article examines methodological dilemmas surrounding entrée, emotion, and epistemology that can arise when conducting qualitative research in carceral settings. We address how our research team navigated consent and presentations of self for maintaining access; how they managed empathy and the emotional toll of conducting research in adversarial settings; and how conflicting narratives raised questions about data validity and knowledge construction. Analysis reveals how institutional power dynamics shape behind-the-scenes methodological decisions we make during fieldwork. Without open discussion, researchers risk perpetuating the opacity we seek to diffuse and replicating the power dynamics we aim to objectively document within total institutions.